PENGEMBANGAN MODUL BERBASIS DAERAH TRENGGALEK UNTUK MENUMBUHKAN SIKAP PEDULI LINGKUNGAN - Kardiana Metha Rozhana; Moh Farid Nurul Anwar (Jurnal Bidang Pendidikan Dasar, 2019)
Abstract The teacher's difficulties in teaching are weaknesses in preparing thematic lesson plans and the lack of adequate learning resources for students. The purpose of this development and research is to provide facilities and new innovations for elementary school teachers in developing module teaching materials. The hope is that this module can be used as an additional supplement for students and as an effort to apply environmental awareness as found in character education. This study used the research and development method of Borg & Gall. The results of the feasibility validation from the experts showed that the percentage of 89.4% was feasible. While aspects of the application of teachers and students of module products through questionnaires showed an average percentage of 92.5% with very good criteria and could be used without revision. While the effectiveness of modules is seen from two aspects, namely learning outcomes with a mean percentage of 95.2% showing complete learning and learning activities showing active information with a percentage of 77.4%. While the value of environmental care attitude shows a percentage of 3%, namely a good attitude towards the environment of residence. abstrak Kesulitan guru dalam mengajar yaitu kelemahan dalam menyusun RPP tematik dan kurangnya sumber belajar yang memadahi bagi siswa. Tujuan pengembangan dan penelitian ini yaitu memberikan kemudahan dan inovasi baru bagi guru SD dalam mengembangkan bahan ajar modul. Harapannya modul ini dapat dijadikan suplemen tambahan bagi siswa dan sebagai upaya menerapkan sikap peduli lingkungan sebagaimana yang terdapat dalam pendidikan karakter. Penelitian ini menggunakan metode penelitian dan pengembangan Borg & Gall. Hasil validasi kelayakan dari para ahli menunjukkan persentase 89,4% layak digunakan. Sedangkan aspek keterterapan guru dan siswa produk modul melalui angket menunjukkan persentase rata-rata 92,5% dengan kriteria sangat baik dan dapat digunakan tanpa revisi. Sedangkan keefektifan modul dilihat dari dua aspek yaitu hasil belajar dengan persentase rerata 95,2% menunjukkan pembelajaran tuntas dan aktivitas belajar menunjukkan keterangan aktif dengan persentase 77,4%. Sedangkan nilai sikap peduli lingkungan menunjukan persentase 3% yaitu sikap baik terhadap lingkungan tempat tinggal.